PERAN DIGITAL MARKETING DALAM MENINGKATKAN DAYA SAING UMKM DI INDONESIA: TINJAUAN LITERATUR TERBARU - M. Son Aghni; Luthfy Purnanta Anzie (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in Indonesia's economy, yet they continue to face competitiveness challenges in the digital era. This study aims to systematically examine the role of digital marketing in enhancing the competitiveness of MSMEs in Indonesia. Utilizing a Systematic Literature Review (SLR) method, eight relevant academic journals published between 2022 and 2025 were analyzed. The analysis involved reviewing each study's objectives, methods, findings, and the digital strategies applied. The results reveal that digital marketing significantly contributes to increasing visibility, promotional efficiency, and market expansion for MSMEs. The most frequently used platforms include social media, online food delivery services, and AI-based digital tools. However, various obstacles were identified, such as low digital literacy and limited infrastructure support. This research offers practical insights into effective digital marketing strategies and provides recommendations for stakeholders to strengthen the digital capabilities of MSMEs in Indonesia.